TEACHING READING THROUGH MIND MAPPING STRATEGY IN NARRATIVE TEXT FOR READING COMPREHENSION - Ramadhan, Syahrur; ., Regina; Salam, Urai (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: This research aimed at activity and the effectiveness of the use of mind mapping strategy in improving students’ skill in teaching reading for narrative text to Tenth Grade Students of SMA Ki Hajar Dewantara in Academic Year 2014 / 2015. The research method used is a Pre ExperimentalResearch.The study sample is 37 students. Basedon theanalysisof the data, the students’ mean score of effectiveness was 83.5. This score showed a significance difference to the pretest result which was 39.5. Furthermore, the Effect Size computation where the value of ES was 5.2(categorized as high).It is therefore, the Alternative Hypothesis (Ha) is accepted and Null Hypothesis is rejected and it can be concluded that Mind Mapping strategy was effective in teaching reading comprehension in narrative text. Keywords: Mind Mapping, Reading, Narrative Text. Abstrak: Penelitian ini bertujuan untuk mengetahui tingkat keefektifan menggunakan strategi Mind Mapping didalam pengajaran membaca pada teks narasi untuk siswa kelas X SMA Ki Hajar DewantaraPontianak. Metode penelitian yang digunakan adalah pre eksperimental. Sampel penelitian adalah 37 siswa. Berdasarkan analisis data, nilai rata-rata siswa efektif adalah 83,5. Nilai ini menunjukan signifikan yang berbeda dengan tes tertulis (pre-tes) yang mana hasilnya 39,5. Selanjutnya, perhitungan ukuran efek (effect size) dimana nilai dari ukuran efek adalah 5,2 (kategori tinggi) .Oleh karena itu, alternative hipotesis adalah diterima dan nol hipotesis adalah ditolak dan bisa disimpulkan bahwa strategi Mind Mapping adalah efektif didalam pengajaran teks narasi. Kata Kunci: Mind Mapping, membaca, teks narasi